2017
DOI: 10.1002/jmv.24858
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection and atherosclerosis risk: A meta‐analysis

Abstract: Human cytomegalovirus (HCMV) infection is an important risk factor for atherosclerosis (AS). Numerous studies have been conducted to analyze the association between HCMV infection and risk of AS, but no clear consensus has been reached. So the objective of this paper was aimed to demonstrate the relationship between HCMV and AS by doing a meta-analysis. Relative literature was searched through the electronic databases PubMed, Embase, and CNKI. Data were accurately assessed and analyzed independently by two inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…56 Evaluation of the immune response to cytomegalovirus infection initially did not reveal an effect of seropositivity to cytomegalovirus on the development of atherosclerosis. 13,14,57 However, the results of seroepidemiological studies were also controversial, with further studies that found a positive correlation between the increased titer of antibodies to cytomegalovirus and the development of atherosclerosis, [23][24][25]58,59 cardiovascular events, 60,61 and mortality, 62,63 even when adjusted to other traditional cardiovascular risk factors. These controversies in seroepidemiological studies as well as the low level of cytomegaloviral DNA found in atherosclerotic plaques and later in peripheral blood mononuclear cells of patients with cardiovascular diseases 64 could be explained by the occasional detection of the latent infection in these studies, rather than productive viral infection, whereas only the latter correlates with plaque destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…56 Evaluation of the immune response to cytomegalovirus infection initially did not reveal an effect of seropositivity to cytomegalovirus on the development of atherosclerosis. 13,14,57 However, the results of seroepidemiological studies were also controversial, with further studies that found a positive correlation between the increased titer of antibodies to cytomegalovirus and the development of atherosclerosis, [23][24][25]58,59 cardiovascular events, 60,61 and mortality, 62,63 even when adjusted to other traditional cardiovascular risk factors. These controversies in seroepidemiological studies as well as the low level of cytomegaloviral DNA found in atherosclerotic plaques and later in peripheral blood mononuclear cells of patients with cardiovascular diseases 64 could be explained by the occasional detection of the latent infection in these studies, rather than productive viral infection, whereas only the latter correlates with plaque destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory artery disease that is characterized by alterations in the levels of lipids and other metabolites is the most important cause of cardiovascular diseases (CVDs). A recent meta‐analysis showed that HCMV infection was also an important risk factor for atherosclerosis . ECs, leukocytes, and intimal smooth muscle cells are the major players in the development of this disease .…”
Section: Pathogenesismentioning
confidence: 99%
“…However, there is no evidence of viral binding to these receptors in HCMV‐mediated angiogenesis. EGFR is required for the HCMV‐induced angiogenic response, whereas the Src family of tyrosine kinases is only partially required . Furthermore, EGFR‐mediated and integrin‐mediated signaling (via Src) is rapidly activated in ECs after infection, suggesting that the engagement of such signaling after viral binding is intimately associated with functional changes in ECs …”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations